Element of activities in traditional street in Malaysia for attraction; A case study of Kuala Lumpur - Nor Haslina Ja’afar,; I.M.S. Usman,; M.M.Tahir,; M.F. Irfan Mohd Nor, (Penerbit UKM, 2008)
In a rapid urbanization, there are characters of traditional streets in old towns that still attract visitors until today. This type of street creates a sense of place or “genious loci” with a unique setting. Apart from this, the goal of this research is to determine the element(s) of traditional street in Malaysia that attracts visitors from a user point of perception. The objective of this research is to identify and investigate the element(s) that have been mentioned by users in attracting them to the street. Mix methodologies were used, namely the qualitative method as a major approach and followed by quantitative method as a supporting data. In-depth interviews, photo recognitions and observations were the techniques applied for qualitative data. 21 respondents (users) were selected for the study conducted